The Influence of E-Service Quality and E-trust on Repurchase Intention through E-Satisfaction at Shopee (A Case Study of International Students in Malang) - Patrick, Rafanomezanjanahary Augustin; Seriño, Moises Neil V (Ekonomi Bisnis, 2024)
This study examines the correlations service quality, satisfaction, repurchase intention among online shoppers particularly international students in Malang. It also seeks to explore the indirect convincing of e-service quality on repurchase intention through e-satisfaction and the indirect effects of e-trust on repurchase intention through e-satisfaction. The study used a purposive sample approach, a non-probability sampling strategy. The respondents of the study include a total of 112 international students in Malang who are active online shoppers The research data was collected through online surveys via social media. The research data was analysed using structural equation modelling (SEM) and partial least squares (PLS) 3.0. Data analysis involves several key phases: validity, reliability, and hypothesis testing. The study's findings support the idea that e-satisfaction is positively correlated with e-service quality. E-trust positively influences e-satisfaction, which directly influences repurchase intent. The quality of e-services positively influences repurchase intent, and e-trust favourably influences repurchase intention.